A voz de Dilma: performances oratórias e discursos sobre a fala pública da Presidenta - Casanova, Nicolle de Brito Conceição (2018)
Theoretically based on French Discourse Analysis, derived from the works of Michel Pêcheux and his group, this research proposes to analyse Dilma Rousseff’s pronouncements and discourses on her public speech as conveyed by the brazilian media, giving particular attention to the uses and representations of her voice, in order to comprehend the establishment and consolidation of the consensus according to which she would be a poor speaker. Henceforth, we propose to question this consensus by examining the oratory performances and media discourses on this performances, in the interest of demonstrating that not only do such discourses condition the public speech performances of the subjects of a society, in general, and Dilma’s performances, in particular, but also produce the descriptions, comments and evaluations on these performances. In other words, these discourses elaborate, consolidate and can eventually transform the appreciation and depreciation that comes from the public pronouncements’ listening. Moreover, the discursive dynamic that works for the role these sayings play in the framing of the enthusiasms, preferences, indiferences and revulsions in the reception and judgement of public speech also works for the attribution and recognition of the speakers’ charisma: such as eloquence itself, it should thus be conceived as a construction that is processed in history, society and discourse. In pursuit of this purpose, we work on a corpus that consists, on one hand, of Dilma’s pronouncements conveyed by television between 2010 and 2017, covering the period in which she speaks as a presidential candidate, as President and as former President and, on the other hand, on journalistic articles extracted from brazilian newspapers and magazines in national circulation, presented in the form of varied discursive genres (news, reports, editorials, opinion articles and informative notes) and published in different sections and supplements of the newspapers Folha de São Paulo e O Estado de São Paulo and of the magazines Veja and Carta Capital.